Exploring audit quality at the Inland Revenue Board Malaysia (Global Business Management Review (GBMR), 2022)
Audit quality at the Inland Revenue Board Malaysia (IRBM) is a crucial element in the audit process to ensure no violation of tax reporting by the taxpayers. Hence, it is important to understand whether tax auditors perceive audit quality equally.  Furthermore, recognizing the level of audit quality is also important to assist the tax authority in strategizing their efforts. This triggers researchers to embark on this exploratory study through document review and interviews. Data gathered were analysed using descriptive and thematic analysis. Results indicate that there is different perception of audit quality among tax officers, namely competency to detect the amount of audit settlement, audit settlement within the time frame and the achievement of the given key performance indicators (KPIs). The findings further indicate that the level of audit quality is quite alarming particularly with reference to the number of aging cases. The findings from this study provide an insight to the IRBM in their effort to streamline the direction of the tax auditors in improving audit quality.